2019
DOI: 10.3390/molecules25010141
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Derived Molecules α-Boswellic Acid Acetate, Praeruptorin-A, and Salvianolic Acid-B Have Age-Related Differential Effects in Young and Senescent Human Fibroblasts In Vitro

Abstract: Testing and screening of plant-derived molecules on normal human cells in vitro is a widely used approach for discovering their eventual health beneficial effects for human ageing and longevity. As little is known about age-associated differential effects of such molecules, here we report that young (<25% replicative lifespan completed) and near-senescent (>90% replicative lifespan completed) human skin fibroblasts exposed for 1-15 days to a wide range of concentrations (0.1-100 µM) of the three selected phyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Indeed, rosmarinic acid increases lifespan in C. elegans [99] and in an animal model of familial amyotrophic lateral sclerosis [179] and protects cells from UV radiation-induced aging [180,181] as well as in other models of cell senescence [102,[182][183][184]. Salvianolic acid B [185][186][187] and apigenin [188][189][190][191][192][193][194] also exert strong anti-aging effects. Considering the results of the isolated compounds, it would be expected that the HRW would prevent cell senescence; however, our results show that the HRW alone induces cell senescence, thus suggesting that these compounds can have antagonistic effects when in a complex mixture.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, rosmarinic acid increases lifespan in C. elegans [99] and in an animal model of familial amyotrophic lateral sclerosis [179] and protects cells from UV radiation-induced aging [180,181] as well as in other models of cell senescence [102,[182][183][184]. Salvianolic acid B [185][186][187] and apigenin [188][189][190][191][192][193][194] also exert strong anti-aging effects. Considering the results of the isolated compounds, it would be expected that the HRW would prevent cell senescence; however, our results show that the HRW alone induces cell senescence, thus suggesting that these compounds can have antagonistic effects when in a complex mixture.…”
Section: Discussionmentioning
confidence: 99%
“…Salvianolic acid B exerts excellent protective effects not only on damaged organs and tissues, but also on different types of tumors, inflammation, depression, and spinal cord injury by improving the corresponding indices. Studies have demonstrated that salvianolic acid B can protect against coronavirus disease 2019 [ 224 , 225 ], exerts anti-aging effects [ 226 , 227 ], and can be used in the treatment of uremic syndrome [ 228 ]. Recently, commercially available dosage forms based on salvianolic acid B mainly include injections containing Salvia miltiorrhiza polyphenol acid for injection and salvianolic acids for injection.…”
Section: Discussionmentioning
confidence: 99%